Rancang Bangun Dan Analisa Quality Of Services (QoS) VoIP Server Menggunakan Briker Dengan Memanfaatkan Trunk Dan Interactive Voice Respons (IVR) Di AirNav Padang - Adibasyah, Muhammad (Telekontran : Jurnal Ilmiah Telekomunikasi, Kendali dan Elektronika Terapan, 2023)
In the digital era, VoIP communication technology is popular due to its low cost and good voicequality. At the AirNav Padang, communication is still manual using conventional telephones, which isconsidered expensive and less effective. The solution is to implement VoIP through the local network, utilizingcomputers, smartphones, headphones, and analog phones for cost efficiency and cross-divisioncommunication. Similar research has addressed cost issues with VoIP. However, VoIP implementationrequires good Quality of Service (QoS) to avoid delays, jitter, and packet loss that can disrupt communication.This research focuses on the design and analysis of QoS for a VoIP server with Briker, trunk, and IVR at thePerum LPPNPI Padang Branch Subsidiary Office. QoS measurements show an average delay of around22.754 ms, an average jitter of about 3.572 ms, and an average packet loss of about 0.04% for calls betweenclients. Meanwhile, for calls with trunk and IVR, the average delay is approximately 21.756 ms, the averagejitter is around 5.402 ms, and the average packet loss is about 0.05%. This solution can optimize cross-divisioncommunication with low costs and high efficiency.